Tren Gaya Hidup Modern Dan Pengaruhnya Terhadap Konsumsi Sprite Pada Generasi Milenial Dan Gen Z - Delia Azzahra, Rushal; Budi Harto; Andina Dwijayanti (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2025)
This research is motivated by the significant changes in people's consumption habits influenced by modern lifestyles, especially among millennials and Gen Z. In particular, urbanization, technological advancements, and the increasing awareness of faster and more convenient ways of consuming are driving these changes. In particular, urbanization, technological advancements, and a growing awareness of faster and more convenient ways of consuming are driving these changes. Although many previous studies have discussed the influence of modern lifestyles on consumption behavior, there is still a lack of comparative analysis between millennials and Gen Z generations. The methodology used in this research is a survey by distributing questionnaires to 115 respondents who meet the criteria, to measure the influence of modern lifestyles on Sprite consumption. The results showed a strong positive correlation between modern lifestyle and Sprite consumption, with a correlation value of 0.773 (p < 0.001), and an increase in Sprite consumption along with an increase in one unit of modern lifestyle. In addition, this study found that the validity and reliability of the questionnaire used was also assured with Cronbach's Alpha values above 0.7. The implications of this study provide valuable information for companies to design more effective marketing campaigns that highlight the lifestyle factors that influence consumer choices.